Management of aphthous-like ulcer induce by trauma in patient with thalassemia beta intermedia: a case report - Riyanto, Dahlia; Soebadi, Bagoes; Hadi, Priyo; Radithia, Desiana (Hasanuddin University, 2020)
Objective: Thalasemia is an inherited blood diseases cause which abnormalities systemically and intraorally. This case report to discuss management of Aphthous-Like Ulcer in 24 year old man with Thalasemia Î² Intermedia and need blood transfusion every month. Ulcer occured 2 days before transfusion.Methods: Based on history, clinical examination, hematologi and ferritin tests.Results: The diagnosis was Aphthous Like ulcer induce by trauma. Patient was treated using anti-inflammatory mouthwash and recovery was achieved within 3 weeks follow-up. Conclusion: Management of oral manifestation in Thalasemia patient need multidiciplinary approach to obtain successful therapy.